O4A.1 Night shiftwork, dna methylation, and telomere length in female nurses. (April 2019) - Carugno, Michele; Crespi, Eleonora; Bollati, Valentina; Tarantini, Letizia; Dioni, Laura; Ferrari, Luca; Bonzini, Matteo; Consonni, Dario; Maggioni, Cristina; Costa, Giovanni; Pesatori, Angela Cecilia
Abstract : Introduction: Studies on female nurses have reported a higher breast cancer risk among night shift (NS) workers, without a clear understanding of the underlying biological mechanisms. Aim: To assess the association between night shiftwork and molecular alterations potentially related to a higher carcinogenic risk, in details: DNA methylation of estrogen receptor (ER-Alpha, ER-Beta) and tumor suppressor (BRCA1, BRCA2, p53, p16) genes, global DNA methylation estimated on repeated elements (LINE-1, Alu), and telomere length (TL). Methods: 46 female nurses who had been working in NS for at least two years in a Hospital in Milan, Italy, were matched by age (30–45 years) and length of service (at least 5 years) with 51 female colleagues not working in NS. Each subject was administered a structured questionnaire and withdrawn a 12 ml blood sample. We applied linear regression models adjusted for age, BMI, smoking habit, parity, and oral contraceptive use. Results: Currently working in NS (yes/no) was associated with hypomethylation of ER-Alpha (β: −1.635, 95% CI: −2.715; −0.554). When examining both current and former NS workers, the number of years (NY) in NS was associated with hypermethylation of Alu (β: 0.078, 95% CI: 0.016; 0.138). After graphical inspection of the association between NYNS and TL, we classified the study population according to NS duration (<15 vs.≥15 years). Among workers with at least 15 years of NS, NYNS was associated with TL reduction (β: −0.065, 95% CI: −0.122; −0.008) and hypomethylation of ER-Alpha (β: −2.009, 95% CI: −3.164; −0.853). Association between NYNS and hypermethylation of p53, p16, BRCA1, BRCA2, and LINE-1 was much stronger, albeit not significant, in workers with at least 15 years of NS. Conclusions: Our findings show NS-associated epigenetic alterations that might be involved in processes such as cellular aging, genomic instability, and cancer development.